2003
DOI: 10.1080/01449290301781
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of volitional control in information ethics

Abstract: The main motivation of this research is how the issue of volitional control might affect the application of the theory of planned behavior (TPB) to research decisions related to information ethics. Specifically, a TPBbased model provides the best fit to the sample collected for the present study. In this model, the contribution of both the attitude and perceived behavioral control to the intention is shown to fluctuate depending upon the degree of volitional control concerning the targeted behavior. As the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…When the efficacy of precautionary measures is perceived as high, people have more positive attitudes about security policies and practices that include the collection of personal information and monitoring of their behaviors (Hsu & Kuo, 2003;Thomas, 2004). Alternatively, if the efficacy of the precautionary measures is low or is perceived to deliver only a small incremental degree of benefit compared to the personal costs, people have poorer attitudes about such policies and practices (Pechmann et al, 1993).…”
Section: Efficacy and Monitoringmentioning
confidence: 98%
“…When the efficacy of precautionary measures is perceived as high, people have more positive attitudes about security policies and practices that include the collection of personal information and monitoring of their behaviors (Hsu & Kuo, 2003;Thomas, 2004). Alternatively, if the efficacy of the precautionary measures is low or is perceived to deliver only a small incremental degree of benefit compared to the personal costs, people have poorer attitudes about such policies and practices (Pechmann et al, 1993).…”
Section: Efficacy and Monitoringmentioning
confidence: 98%
“…Most of these organizational studies have indicated benefits from preventative measures on information security preservation outcomes. Nevertheless, these investigations have tended to either impose a particular system of situational ethics (Harrington, 1996; Hsu & Kuo, 2003; Kurland, 1995) or to utilize theory for predictive models of security effectiveness in which there is a “dominance of technical and functionalist preconceptions, essentially because most methods have been grounded in a particular well‐defined reality, i.e. that of the military” (Dhillon & Blackhouse, 2001, p. 148), leaving us with a gap in our understanding about the behavior related to information security, particularly in relation to their underlying behavioral causes (Phelps, 2005; Workman & Gathegi, 2005).…”
Section: Previous Literature Theory and Hypothesesmentioning
confidence: 99%
“…This means that managers must clearly define and explain the processes and purposes of surveillance practices as well as the countermeasures used in helping to protect the integrity and security of the employee information (Thomas, 2004). (2) Managers need to constantly convey the necessity and importance of the surveillance practices because when people perceive greater benefits, they are more likely to accept these practices and correspondingly have improved attitudes (Hsu and Kuo, 2003). (3) Managers need to regularly review and discuss with employees the surveillance practices to be sure of fairness and equal treatment.…”
Section: Discussionmentioning
confidence: 99%